Analysis of Hot-Air Supplemented Solar Drying Using Computational Fluid Dynamics Technique - Aduewa, Taiwo; Oyerinde, Ajiboye (PT Mattawang Mediatama Solution, 2022)
Energy is a crucial input in the process of economic, social and industrial development of any nation. Fluctuating solar insolation and late sunrise hour has led to poor quality dried biological material production. A simulation of hot-air supplemented solar dryer (HSSD) designed for such purpose is presented for temperature distribution based on direct solar irradiation of 1423 W/m2 of Akure, Nigeria (5.304º Latitude 7.258º Longitude). The environmental conditions in the hybrid dryer were measured during a day of operation. The model of the dryer was created and a numerical model was established to allow replicating the internal environmental conditions of the dryer. The airflow, temperature, radiative heat flux and other parameters inside the HSSD system were simulated using computational fluid dynamics (CFD) approach. The simulated result was compared with the calculated and estimated parameter values for the HSSD. The simulated air-flow pattern and temperature distribution on the horizontal and vertical planes in the drying chamber were analyzed and the results revealed spatial homogeneity of drying air condition. However, there is higher velocity profile at the outlet vent due to buildup of hot air at outlet vent. There was relatively low interference of external temperature in the drying chamber.